Pemanfaatan buah durian menjadi selai Dampo’ sebagai upaya pemberdayaan masyarakat di Desa Betao Riase - Muh Zulkifli; Mutiara Wulandari; M. Aldi Muhtadibillah A; Surya Baskara Jaya; Mentari Nur Arafah; Muh Rigan Yusri; Rahmat; M. Adely Ihsan M; Mardatillah; Eka Mawarni (P3HKI - Universitas Muhammadiyah Parepare, 2022)
Betao Riase Village, located in Sidenreng Rappang Regency, is known as a center for local durian production. However, during the peak harvest season, the village faces the issue of fruit oversupply, rendering a large portion of the durian unmarketable. To address this, students from the Community Service Program (KKN) of Universitas Muhammadiyah Parepare conducted a training on producing Dampo' durian jam as a form of product diversification. This initiative aims to enhance the community's knowledge and skills in processing durian into value-added products while creating opportunities for home-based entrepreneurship using local resources. The training was attended by 30 participants, consisting of housewives and members of farmer groups. The training process included material selection, processing, and basic packaging. The results showed strong enthusiasm from the participants and successful production of durian jam with a distinctive taste and promising market potential. Some participants have even started selling their products through local village bazaars. Beyond extending the shelf life of the fruit, the activity fostered entrepreneurial spirit and productive use of local potential. Further training in food packaging and digital marketing is recommended to ensure business sustainability. This activity highlights the strategic role of university students as agents of community empowerment in developing rural economies based on local potential.